2013
DOI: 10.1038/bcj.2013.18
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine insulin-like growth factor 1 and stem cell factor but not interleukin 6 support self-renewal of human myeloma cells

Abstract: In this study, we have identified the growth factors supporting myeloma self-renewal in eight myeloma cell lines. All cell lines able to form self-colonies displayed constitutive P-AKT and P-ERK1,2 but not P-STAT3 and did not express CD45, suggesting the presence of an insulin-like growth factor 1 (IGF1) loop. We showed that a blocking anti-insulin-like growth factor 1 receptor (IGF1R) monoclonal antibody (mAb) inhibited colony formation in correlation with IGF1R expression and decreased P-AKT. Imatinib or a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…In addition, they found that the increased proliferation of human MM cell lines induced by IL-6 is dependent on the presence of an autocrine IGF-I loop [30]. Furthermore, autocrine IGF-I, but not IL-6, was recently described as being the main self-clonogenic growth factor for myeloma cell lines [99]. Finally, Huang et al .…”
Section: The Igf System In MMmentioning
confidence: 99%
“…In addition, they found that the increased proliferation of human MM cell lines induced by IL-6 is dependent on the presence of an autocrine IGF-I loop [30]. Furthermore, autocrine IGF-I, but not IL-6, was recently described as being the main self-clonogenic growth factor for myeloma cell lines [99]. Finally, Huang et al .…”
Section: The Igf System In MMmentioning
confidence: 99%
“…Specifically, RPMI8226-Luc and UBE6T-7 cells were injected separately in the right and left thighs, respectively (separate inoculation), or injected as a mixture in the right thigh (mixed injection) of NOD/SCID mice ( Figure 13A). The administration of cyclophosphamide (CY) alone, OSI-906 alone, and their combination significantly reduced the viability of MM cells, as determined by luciferase activity, in the separate inoc-A recent report by Chiron et al (34) implicating IGF-1 as an autocrine activator of MM urged us to investigate the role of IGF-1 for CAM-DR using gain-and loss-of-function approaches. We used recombinant IGF-1 (rIGF-1) to examine its effects on druginduced cytotoxicity under stroma-free conditions.…”
Section: Therapeutic Effects Of the Igf-1r Inhibitor Osi-906 In Murinmentioning
confidence: 99%
“…It is not entirely clear at which stage in the development of the disease or exactly which cell populations within the malignant clone are dependent on IL-6 or need additional signals. A recent study suggests that autonomous growth, as assessed by spontaneous colony formation, is regulated by insulin-like growth factor (IGF)-1 and stem cell factor (SCF) rather than IL-6 [40]. IL-6 is also a potent osteoclast-activating factor, and contributes to the development of bone lesions.…”
Section: Role Of Il-6 In the Pathophysiology Of Hematological Tumorsmentioning
confidence: 99%